Distinct transcriptomic and exomic abnormalities within myelodysplastic syndrome marrow cells. Issue 12 (2nd December 2018) - Im, Hogune; Rao, Varsha; Sridhar, Kunju; Bentley, Jason; Mishra, Tejaswini; Chen, Rui; Hall, Jeff; Graber, Armin; Zhang, Yan; Li, Xiao; Mias, George I.; Snyder, Michael P.; et al.
Abstract: To provide biologic insights into mechanisms underlying myelodysplastic syndromes (MDS) we evaluated the CD34 + marrow cells transcriptome using high-throughput RNA sequencing (RNA-Seq). We demonstrated significant differential gene expression profiles (GEPs) between MDS and normal and identified 41 disease classifier genes. Additionally, two main clusters of GEPs distinguished patients based on their major clinical features, particularly between those whose disease remained stable versus patients who transformed into acute myeloid leukemia within 12 months. The genes whose expression was associated with disease outcome were involved in functional pathways and biologic processes highly relevant for MDS. Combined with exomic analysis we identified differential isoform usage of genes in MDS mutational subgroups, with consequent dysregulation of distinct biologic functions. This combination of clinical, transcriptomic and exomic findings provides valuable understanding of mechanisms underlying MDS and its progression to a more aggressive stage and also facilitates prognostic characterization of MDS patients.